Effect and degradation pathway of sulfamethoxazole removal in MBR by PVDF/DA modified membrane - Zhang, Meilin; Li, Shaofeng; Sun, Jian; Sun, Jianping; Wang, Lei; Zhao, Rui (Frontiers in Environmental Science, 2023)
To reduce the hazard of sulfamethoxazole (SMX) to the water ecology, the removal mechanism of SMX in wastewater was revealed. This study evaluated the PVDF/DA modified membrane in the MBR toward the removal and degradation of SMX as a recalcitrant micropollutant. A strategy of dopamine for surface modification of polyvinylidene fluoride (PVDF) membrane was proposed, and PVDF/DA membrane was prepared. Subsequently, PVDF/DA was run in a membrane bioreactor (MBR) for 60 days, and the reactor could produce good removal ability for SMX after certain acclimation. When the SMX concentration increased from 0.5 mg/L to 2 mg/L, liquid chromatography was used for analysis, and the results showed that the average removal rate was above 85%. The removal effect of COD and NH4+-N and the degree of membrane fouling were also evaluated. By measuring the extracellular polymer (EPS) content, the results showed that after 30 days of operation, the protein and polysaccharide contents in the cake layer on the surface of the PVDF membrane were 1.35 times and 1.49 times that of PVDF/DA membrane, respectively, and the PVDF/DA membrane could alleviate membrane fouling, thereby improving the service life of the membrane and reducing its operating cost. Finally, degradation by-products are evaluated to achieve deeper insight into the degradation mechanisms in the MBR process.